Association of dietary macronutrient composition and non-alcoholic fatty liver disease in an ageing population: the Rotterdam Study. Issue 6 (31st July 2018) - Alferink, Louise JM; Kiefte-de Jong, Jessica C; Erler, Nicole S; Veldt, Bart J; Schoufour, Josje D; de Knegt, Robert J; Ikram, M Arfan; Metselaar, Herold J; Janssen, Harry LA; Franco, Oscar H; Darwish Murad, Sarwa
Abstract : Objective: A healthy lifestyle is the first-line treatment in non-alcoholic fatty liver disease (NAFLD), but specific dietary recommendations are lacking. Therefore, we aimed to determine whether dietary macronutrient composition is associated with NAFLD. Design: Participants from the Rotterdam Study were assessed on (1) average intake of macronutrients (protein, carbohydrate, fat, fibre) using a Food Frequency Questionnaire and (2) NAFLD presence using ultrasonography, in absence of excessive alcohol, steatogenic drugs and viral hepatitis. Macronutrients were analysed using the nutrient density method and ranked (Q1–Q4). Logistic regression analyses were adjusted for sociodemographic, lifestyle and metabolic covariates. Moreover, analyses were adjusted for and stratified by body mass index (BMI) (25 kg/m 2 ). Also, substitution models were built. Results: In total, 3882 participants were included (age 70±9, 58% female). NAFLD was present in 1337 (34%) participants of whom 132 were lean and 1205 overweight. Total protein was associated with overweight NAFLD after adjustment for sociodemographic and lifestyle covariates (ORQ4vsQ1 1.40; 95% CI 1.11 to 1.77). This association was driven by animal protein (ORQ4vsQ1 1.54; 95% CI 1.20 to 1.98). After adjustment for metabolic covariates, only animal protein remained associated with overweight NAFLD (ORQ4vsQ1 1.36; 95% CI 1.05 to 1.77). Monosaccharides and disaccharides were associated with lower overall NAFLD prevalence (ORQ4vsQ1 0.66; 95% CI 0.52 to 0.83) but this effect diminished after adjustment for metabolic covariates and BMI. No consistent associations were observed for fat subtypes or fibre. There were no substitution effects. Conclusion: This large population-based study shows that high animal protein intake is associated with NAFLD in overweight, predominantly aged Caucasians, independently of well-known risk factors. Contrary to previous literature, our results do not support a harmful association of monosaccharides and disaccharides with NAFLD.